The Effect of Savings Growth, Deposits, Credit, Credit Interest Rate and Cash Turnover on Profit Growth in Savings and Loans Cooperative in North Denpasar Year 2017 – 2019 - Putu Kepramareni; Sagung Oka Pradnyawati; Ni Made Dwika Sari; Yura Karlinda Wiasa Putri (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
This study aims to examine and obtain empirical evidence from the effect of savings growth, deposits, credit, credit interest rates and cash turnover on profit growth in Savings and Loans Cooperatives in North Denpasar in 2017-2019. The population of the data in this study were all Savings and Loans Cooperatives located in North Denpasar and registered with the Denpasar City Cooperatives and Micro Small Medium Enterprises (MSME) Service in 2017-2019. The sample were select by used purposive sampling method. The sample in this study were 16 cooperatives with 48 observations. Multiple linear regression analysis is needed to process the data in this study. And the research results are obtained as follows: saving growth variable, deposit growth and cash turnover have no effect on profit growth, while credit growth and credit interest rates have a positive effect on profit growth. The implication of this research is that the sample selection is limited to one area, namely North Denpasar, so the results cannot be generalized and are limited to the form of savings and loan cooperatives only.